1999
DOI: 10.1021/es9905593
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Degradation of a Model Oil Compound in Soil Using a Liquid Foam-Microbe Formulation

Abstract: This paper describes the development of a protein-based foam formulation and subsequent investigations into its suitability to enhance the degradation of a model hydrocarbon (n-hexadecane) using novel bench-scale soil microcosms. High-density protein-based foam concentrates based upon those developed by the fire-fighting industry were selected for experimental investigation. Using crude protein hydrolysate as a starting material, a foam formulation was developed with properties suitable for bioremediation stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…In the liquid phase, the toluene concentrations also increased rapidly, but the values were much lower than the theoretical equilibrium concentration calculated using the Henry's law constant at the elevated toluene-loading rate, implying that active microorganisms could effectively biodegrade toluene, even under this transient-loading condition. However, the BFR system in this study appeared not to possess sufficient sorption capacity to dampen the inlet-loading changes, since the surfactant concentration was maintained at less than its critical micelle concentration and organic chemicals such as oleyl alcohol were not added to increase sorption capacity in the liquid phase [13,15]. As a result, the addition of chemicals capable of absorbing pollutants needs to be considered if the BFR system is frequently subjected to dynamic-loading conditions.…”
Section: Transient-loading Testmentioning
confidence: 90%
See 1 more Smart Citation
“…In the liquid phase, the toluene concentrations also increased rapidly, but the values were much lower than the theoretical equilibrium concentration calculated using the Henry's law constant at the elevated toluene-loading rate, implying that active microorganisms could effectively biodegrade toluene, even under this transient-loading condition. However, the BFR system in this study appeared not to possess sufficient sorption capacity to dampen the inlet-loading changes, since the surfactant concentration was maintained at less than its critical micelle concentration and organic chemicals such as oleyl alcohol were not added to increase sorption capacity in the liquid phase [13,15]. As a result, the addition of chemicals capable of absorbing pollutants needs to be considered if the BFR system is frequently subjected to dynamic-loading conditions.…”
Section: Transient-loading Testmentioning
confidence: 90%
“…Instead of utilizing a fixed biofilm, several innovative approaches using suspended microorganisms have been proposed for the biological treatments of VOCs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This feature coupled with a large interfacial area arising from the small bubble size has resulted in its applications in separation processes [5][6][7][8][9]. It has been suggested that microbubble dispersions can enhance bioremediation by effectively increasing mass transfer of oxygen and nutrients in the subsurface [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…These foams can be applied as a blanket over a contaminated site which, in turn, can enhance hydrocarbon removal (Stabnikova et al . 1996; Ripley et al . 2000).…”
Section: Introductionmentioning
confidence: 99%